2015
DOI: 10.4192/1577-8517-v15_6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Theory of Planned Behavior, Technology Acceptance Model, and Information System Success Model on the Acceptance of Electronic Tax Filing System in an Emerging Economy

Abstract: Abstract. Adoption studies on electronic tax-filing system using data from emerging nations are rare. The present paper studies the influence of perceived ease of use, perceived usefulness, and user satisfaction on taxpayers' behavioral intentions to adopt electronic tax filing services in an emerging economy. For this study, constructs from Theory of Planned Behavior (Ajzen, 1985(Ajzen, , 1991, Technology Acceptance Model (Davis, 1989), and Information System Success Model (DeLone & McLean, 1992) are used. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
0
15
0
12
Order By: Relevance
“…Palumbo (2015) argues that efficient infrastructure that facilitates accessibility and mobility is significant to develop a high-quality tourist offer. Gupta et al (2015) found that convenience of service is positively associated with taxpayer satisfaction with e-filing. Therefore, we argue the quality of internet access, the bandwidth, the cost of access, availability of choices in service providers, and assurance of internet securityall are key motivating factors for organizations and users to use ICT for conducting financial (e.g., purchase and sales), regulatory and compliance transactions (e.g., reporting of environmental conditions, filing taxes).…”
Section: Hypothesis 2b: the Extent Of Ict Diffusion Is An Antecedentmentioning
confidence: 96%
See 1 more Smart Citation
“…Palumbo (2015) argues that efficient infrastructure that facilitates accessibility and mobility is significant to develop a high-quality tourist offer. Gupta et al (2015) found that convenience of service is positively associated with taxpayer satisfaction with e-filing. Therefore, we argue the quality of internet access, the bandwidth, the cost of access, availability of choices in service providers, and assurance of internet securityall are key motivating factors for organizations and users to use ICT for conducting financial (e.g., purchase and sales), regulatory and compliance transactions (e.g., reporting of environmental conditions, filing taxes).…”
Section: Hypothesis 2b: the Extent Of Ict Diffusion Is An Antecedentmentioning
confidence: 96%
“…Poel and Marneffe (2016) while examining the potential cost saving in Belgium in using electronic invoicing found that individuals have significant concerns regarding the safety of e-invoicing. Gupta et al (2015) found that perceived risk in online tax filing is negatively associated with taxpayers' behavioral intention to adopt online tax filing. Based on the foregoing discussion one can argue that, a widespread availability of internet access, reliable network connections, affordable prices, and implementation of adequate security protocols in the network and web technologies are likely to assure users to conduct transactions using the web, thus facilitating digital maturity.…”
Section: Maturity Of Ict Diffusionmentioning
confidence: 97%
“…In the new technology usage-related literature, multiple studies adopted the TPB as their theoretical framework for examining users' behavioral intentions that are influenced by attitudes and subjective norms, such as consumers' e-tax filing system adoption behavior (Gupta, Zaidi, Udo, & Bagchi, 2015), health device acceptance of chronic conditioned patients (Sun & Rau, 2015), and users' motivations for multi-tasking interactions with multiple smart devices (Zhang et al, 2013). These studies, however, did not specifically examine consumers' behavioral intentions to use wearable technology.…”
Section: Subjective Normmentioning
confidence: 99%
“…Riset perpajakan menarik diteliti tidak saja terkait pandemi yang berdampak bagi semua pelaku usaha -bisnis dan para wajib pajak secara umum tapi juga temuan ragam riset menunjukan hasil beragam [1]- [6].…”
Section: Pendahuluanunclassified